If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18t = 6 + 6(4t + 11) Reorder the terms: 18t = 6 + 6(11 + 4t) 18t = 6 + (11 * 6 + 4t * 6) 18t = 6 + (66 + 24t) Combine like terms: 6 + 66 = 72 18t = 72 + 24t Solving 18t = 72 + 24t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-24t' to each side of the equation. 18t + -24t = 72 + 24t + -24t Combine like terms: 18t + -24t = -6t -6t = 72 + 24t + -24t Combine like terms: 24t + -24t = 0 -6t = 72 + 0 -6t = 72 Divide each side by '-6'. t = -12 Simplifying t = -12
| y-4.73=7.4 | | r-9.2=-6.8 | | 5x^2-3x+4=x^2-3x+13 | | (x+5)/4=7 | | c+20=15 | | 42=2w+8 | | k(2)+2k-71=9 | | d/20=9 | | k/4=-15 | | Xy-5y-2x+10= | | -6w=108 | | 8x^3y^2+27y^2= | | 6x-30=x-x+4 | | n-20=-19 | | 14x^2-5=0 | | -7+ln(3x)=4 | | 5x^2y^3(3x^2+xy+4y)= | | (s+2)+2s=8 | | -120x+3000=1500 | | -160x+4000=2500 | | 10y-15=0 | | 7x+1-3x-8= | | (X^2-xy+y^2)(x+y)= | | -120x+3000=2500 | | r/4-12=-14 | | 12x^2+x-13=-7 | | -14.875+15+1/3 | | 6x+4=4x+20 | | -12+10z=-30 | | -12c-12=-24 | | 5x-2(3x+4)=-11 | | -9x-8=4x+12 |